2010
DOI: 10.1007/s11284-010-0697-z
|View full text |Cite
|
Sign up to set email alerts
|

Do pollen diets vary among adjacent bumble bee colonies?

Abstract: Central-place foragers, such as bumble bees, are often constrained by their location when collecting resources to provide their young. We compared the resource use (pollen diets) among seven feral colonies of Bombus ardens located in an area of 2.5 · 2.5 km 2 . Because this area was likely to be within their maximum foraging distance, most floral resources could have been accessible to all colonies alike. Similarities in pollen diets among these colonies may suggest that the surrounding resources determine res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
5
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 45 publications
1
5
1
Order By: Relevance
“…Our primary Þnding, that pollen loads are similar between bumble bee individuals within a study region, suggests that competitive forces between colony mates and colonies within a landscape are not strong enough to drive differential foraging patterns. Our results contrast with one past study of pollen analyzed from larval feces, which found that colonies in proximity differed signiÞcantly in the proportional usage of different plant species (Munidasa and Toquenaga 2010). The previous study relied on comparisons of pollen diet between three to four coexisting colonies located within a 2.5-km square area, whereas our study compared pollen collection by wild-caught bees belonging to 12 colonies distributed across a much larger spatial scale.…”
Section: Discussioncontrasting
confidence: 95%
See 2 more Smart Citations
“…Our primary Þnding, that pollen loads are similar between bumble bee individuals within a study region, suggests that competitive forces between colony mates and colonies within a landscape are not strong enough to drive differential foraging patterns. Our results contrast with one past study of pollen analyzed from larval feces, which found that colonies in proximity differed signiÞcantly in the proportional usage of different plant species (Munidasa and Toquenaga 2010). The previous study relied on comparisons of pollen diet between three to four coexisting colonies located within a 2.5-km square area, whereas our study compared pollen collection by wild-caught bees belonging to 12 colonies distributed across a much larger spatial scale.…”
Section: Discussioncontrasting
confidence: 95%
“…Distinct foraging patterns would be beneÞcial at the colony level to obtain diverse and stable nutrient sources. However, we hypothesized that shared colony-level variables such as colony size (Munidasa and Toquenaga 2010) or behavioral attributes (Raine et al 2006) may lead to similar foraging preferences for colony mates while introducing variation between colonies. Our results support this hypothesis, as we found that a majority of ranked preference lists were signiÞcantly similar for colony mates as well as for individuals located at a shared study region.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The fact that in all the other studied cases the relationship between inter-nest distance and prey taxonomic dissimilarity was not significant suggests that the spatial distribution of nests, extremely clumped in B. zonata in 2009, may be the crucial condition favouring the observed trend in this case. Interestingly, in three species of desert ants (Ryti and Case 1984) and in the bumblebee Bombus ardens (Munidasa and Toquenaga 2010), dietary overlap between colonies was positively (and not negatively as in B. zonata) correlated to the mean nearest neighbour distance, suggesting that competition for food regulates the inter-colony distance. However, in B. zonata in 2009 competition for food would probably have no effect on the spatial arrangement of nests, because size difference was also correlated with pairwise diet similarity, probably acting as a buffer against intra-specific competition (see above).…”
Section: Inter-nest Distance and Diet Dissimilaritymentioning
confidence: 98%
“…Notably, studies that have investigated floral resources used by bumblebees were mainly focused on foragers observed at flowers in the field (Williams 1989;Goulson and Darvill 2004;Peat et al 2005;Kleijn and Raemakers 2008;Xie et al 2008;Connop et al 2010). Fewer authors have studied resource allocation directly at the bees' nests (e.g., Kratochwil and Kohl 1988;Peat and Goulson 2005;Munidasa and Toquenaga 2010). Assessing resource use of social bees in the field is, however, prone to sample biases as individual bees tend to (at least periodically) specialize on particular plant species (Heinrich 1976;Heinrich et al 1977;Kratochwil and Kohl 1988) and because colonies are relatively longlived, which increases the spectrum of plant species used for resource allocation.…”
Section: Introductionmentioning
confidence: 99%